Improve anti-biofilm efficacy of ultrasound by modulating the phase transition of exopolysaccharides - Wenyang Xia; Qiuchen Cai; Haoran Wu; Jun Li; Zubin Zhou; Chenglong Huang; Biao Cheng (Ultrasonics Sonochemistry)
This study focused on the adverse sonochemical effect of ultrasound on biofilm extracellular polysaccharide and the adaptive biofilm responses for ultrasound resistance. Results showed ultrasound triggered phase transition of polysaccharides within biofilm from solation to gelation, which induced following biofilm viscoelasticity enhancement, consequential failure of biofilm removal and bacteria killing. Introducing additional cationic polysaccharide, 1.25 % chitosan, inhibited the ultrasound responsive polysaccharides gelation and biofilm viscoelasticity enhancement, exerted synergistic antibacterial (97.40 %) and antibiofilm (96.38 %) effects with 120 W ultrasound combined on S. aureus biofilm, prolonged the preservation time of milk 2.45 times longer compared with ultrasound alone. These findings indicated the possible mechanism and solution to improve ultrasound efficacy on biofilm control and bacteria suppression, exhibit the promising prospect of ultrasound combined strategy in hygiene issues of food and medical industry.